A mitochondria-targeted fluorescent probe for hypochlorite sensing and its application in bioimaging. Issue 8 (9th March 2020) - Yang, Qing; Zhong, Xiuli; Chen, Yingshuang; Yang, Jing; Jin, Can; Jiang, Yuliang
Abstract : A coumarin-diaminomaleonitrile derivative was prepared and used for detecting OCl − in living cells and zebrafish. Its high selectivity, sensitivity and low toxicity indicate that it is an ideal tool for biological applications. Abstract : A coumarin-diaminomaleonitrile derivative (C-DAN ) was designed and prepared. Upon addition of hypochlorite (OCl − ), the fluorescence emission peak of C-DAN at 475 nm was gradually enhanced with a rapid response (within 5 s); meanwhile, the color of the solution changed from dark red to bright yellow which can be observed with the naked eye. Furthermore, owing to its advantages including high selectivity, sensitivity, and low toxicity, our C-DAN probe has been applied for detecting OCl − in living cells and zebrafish, indicating it is an ideal tool for biological applications.